Pattern of Pediatric Dermatoses in a Tertiary Care Hospital of Western Nepal - Yogesh Poudyal; Annu Ranjit; Santosh Pathak; Nagendra Chaudhary (Dermatology Research and Practice)
Pediatric dermatoses are one of the most common presentations in a dermatology clinic and reflect the health and hygiene status of children. The incidence and severity of these skin lesions are influenced by geographical area, seasonal and cultural factors, and socioeconomic status. This study was done to show the prevalence of different pediatric dermatoses in a tertiary care hospital of Western Nepal. Chart reviews of children aged one day to 17 years, presenting to Universal Medical College Teaching Hospital, Nepal, from 1 September 2014 to 30 august 2015, were done. Descriptive analysis and two-sided chi-square test were done. Among 23992 patients visiting the dermatology outpatient department (OPD), 5398 (22.5%) were of pediatric age groups (male/female: 1.2/1); most of them belonged to young teens and teenagers (n=3308; 61.3%). Three most common dermatoses were fungal infections (18.5%), eczema (14.4%), and acne (10.1%). Fungal infections (n=653; 65.4%) and acne (n=284; 51.9%) were common in males, whereas eczema (n=402; 51.7%) was more common in females. Fungal infection (P<0.001), eczema (P<0.001), pigmentation disorders (P<0.001), and acne (P<0.01) were significantly more during summer, while scabies was more in winter (P<0.001). Dermatophytosis, pyoderma, and warts comprised frequently occurring fungal, bacterial, and viral infections, respectively.